Reactive metabolites and AGE-RAGE-mediated inflammation in patients following liver transplantation - Brenner, Thorsten; Fleming, Thomas; Spranz, David Maximilian; Schemmer, Peter; Bruckner, Thomas; Uhle, Florian; Martin, Eike; Weigand, Markus A.; Hofer, Stefan (Mediators of inflammation, 2013)
Recent investigations have indicated that reactive metabolites and AGE-RAGE-mediated inflammation might play an important role in the pathogenesis of ischemia-reperfusion injury in liver transplantation. In this observational clinical study, 150 patients were enrolled following liver transplantation from deceased donors. The occurrence of short-term complications within 10 days of transplantation was documented. Blood samples were collected prior to transplantation, immediately after transplantation, and at consecutive time points, for a total of seven days after transplantation. Plasma levels of methylglyoxal were determined using HPLC, whereas plasma levels of L-arginine, asymmetric dimethylarginine, advanced glycation endproducts-carboxylmethyllysine, soluble receptor for advanced glycation endproducts, and total antioxidant capacity were measured by ELISA. Patients following liver transplantation were shown to suffer from increased RAGE-associated inflammation with an AGE load mainly dependent upon reactive carbonyl species-derived AGEs. In contrast, carboxylmethyllysine-derived AGEs were of a minor importance. As assessed by the ratio of L-arginine/asymmetric dimethylarginine, the bioavailability of nitric oxide was shown to be reduced in hepatic IRI, especially in those patients suffering from perfusion disorders following liver transplantation. For the early identification of patients at high risk of perfusion disorders, the implementation of asymmetric dimethylarginine measurements in routine diagnostics following liver transplantation from deceased donors should be taken into consideration.
Gesehen am 04.12.2020